1991
DOI: 10.1159/000284731
|View full text |Cite
|
Sign up to set email alerts
|

Paranoid Disorders following War Brain Damage

Abstract: Roughly 3,000 war veterans with moderate or severe brain injury have suffered from a psychiatric disturbance. Psychotic disorders are found in approximately 750 cases. The material of this preliminary report consists of the first 100 veterans with paranoid disorders. Delusional psychosis is the most common main diagnosis (28% of veterans), followed by major depression (21 %), delirium (18 %) and paranoid schizophrenia (14 %). Paranoid schizophrenia and paranoid schizophreniform psychosis develop earlier (in 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 0 publications
0
21
1
3
Order By: Relevance
“…In individuals who sustain traumatic brain injury, 4.0% to 8.9% are reported to develop some degree of psychosis [38,39]. Symptoms can range from delusions or hallucinations to expression of odd ideas or aggressive behavior, and may or may not be persistent.…”
Section: Auditory Hallucinations In Medical and Other Psychiatric Conmentioning
confidence: 99%
“…In individuals who sustain traumatic brain injury, 4.0% to 8.9% are reported to develop some degree of psychosis [38,39]. Symptoms can range from delusions or hallucinations to expression of odd ideas or aggressive behavior, and may or may not be persistent.…”
Section: Auditory Hallucinations In Medical and Other Psychiatric Conmentioning
confidence: 99%
“…However, the role of TBI in the genesis of psychosis is a complex matter about which there is considerable scientific uncertainty and disagreement. Although the frequency of psychosis following TBI exceeds that of the general population (Davison & Bagley, 1969;Achte et al, 1969;Achte et al, 1991), there is often a considerable delay between TBI and the onset of psychotic symptoms (Fujii & Ahmed, 1996;Fujii & Ahmed, 2001;Sachdev et al, 2001). Once psychosis develops, the constellation of post-traumatic psychotic symptoms may be difficult to distinguish from those of schizophrenia , complicating the determination of the relationship, where such exists, between an often remote TBI and a recent-onset psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Achte et al [8], in a large Finnish series, reported psychosis in 8.9% of 3552 brain-injured men, with 24% schizophrenia-like, occurring more commonly with mild injuries in younger persons. In a subsequent report, Achte et al [9] studied a sample of 2907 war veterans in Finland who sustained brain injury, and found that 26% had psychotic disorders. In a detailed evaluation of 100 of these veterans, the authors found that 14% had paranoid schizophrenia.…”
Section: Epidemiologymentioning
confidence: 99%